Encyclopedia of peace education - Cromwell, Alexander (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Encyclopedia of peace education, edited by Monisha Bajaj, Charlotte, Information Age Publishing, 2008, 177 pp., US $39.99 (paperback), US $73.99 (hardcover), ISBN 978-1593118983.